Measuring ice hockey skills in a repeated measures testing context: The effects of fatigue on skating efficiency, passing, agility, and shooting - Martini, G.; Brunelle, J. F.; Trudeau, F.; Lemoyne, J. (The Sport Journal, 2018)
Purpose: Ice hockey testing traditionally consists of isolated, skills-specific tests that are performed in less realistic contexts. Global testing approaches should offer an improved assessment of players` skills and performance fluctuations during a hockey game. This study aims to measure ice hockey players` skills and analyze their fluctuations via a protocol that reproduces the demands of a hockey game. Methods: Fifty-nine hockey players (14.6 ± 2.1 years) participated in the study. The protocol involved four repeated measures assessing five components: speed, acceleration, passing, agility, and shooting, with supervised, 2-minute rest periods. Descriptive statistics and repeated measures ANOVAs were used to analyze performance fluctuations. Results: Findings revealed that the best scores were obtained at the first and second repetitions. A significant decline in performance was observed for speed, acceleration, and shooting (p < .01). Inversely, participants seemed to adapt to puck control and passing stations, as they became faster without decreasing skating abilities. Perceived exertion and recovery time increased during the protocol. Conclusions: In summary, performance was affected by fatigue starting the third repetition of the testing protocol, and should be considered when assessing players` skills. This study demonstrated the feasibility of an on-ice testing protocol to evaluate players in a hockey-specific context. Applications in sport: This study demonstrated the feasibility of an "on-ice" testing protocol that represents a more realistic context for measuring players` abilities. Such protocols allow coaches to evaluate the effects of fatigue on multiple determinants associated with performance in ice hockey.